Assessing the impact of Hungary's public health product tax: an interrupted time series analysis - Csákvári, Tímea; Elmer, Diána; Németh, Noémi; Komáromy, Márk; Mihály-Vajda, Réka; Boncz, Imre (Central European Journal of Public Health, 2023)
OBJECTIVES: Imposing taxes on unhealthy goods can generate income, raise people's health awareness, and eventually decrease the prevalence of chronic diseases. Our aim was to assess the impact of Hungary's public health product tax (PHPT) since its implementation in September 2011. Differences in purchasing habits between households with different income statuses were also compared. METHODS: A retrospective, descriptive analysis of tax bases and income was carried out, and an interrupted time series analysis using the generalised least squares method was performed to examine the changes in trends regarding the purchase of taxable products before and after the implementation of the tax. The amount of tax base (in kilograms or litres), income (in HUF and EUR), and annual purchased quantity of food and beverage groups per household were assessed. Data were derived from the National Tax and Customs Administration of Hungary and the Hungarian Household Budget and Living Conditions Surveys. The study sample was composed of households who participated in the surveys (mean = 8,359, SD = 1,146) between 2006 and 2018. RESULTS: The households' tax bases and incomes increased constantly (with a few exceptions). The total revenue was 19.49 billion HUF (67.37 million EUR) in 2012 and 59.19 billion HUF (168.55 million EUR) in 2020. However, the households' purchasing habits did not change as expected. A significant short-term decrease (between 2012 and 2013) in purchasing unhealthy goods was observed for three groups: soft drinks (p = 0.009), jams (p = 0.047), and fruit juices (p = 0.038). Only soft drinks showed a significant decreasing trend in the post-intervention period between 2012 and 2018 (p < 0.001). CONCLUSIONS: We concluded that the PHPT did not decrease households' unhealthy food purchasing trend, although it has a positive effect as it can create revenue for health care and health-promoting programmes.
Keywords: analýza přerušované časové série; nápoje; Beverages; Hungary; Taxes; daně; obchod; Maďarsko; Commerce; Retrospective Studies; retrospektivní studie; lidé; Public Health; Interrupted Time Series Analysis; Humans; veřejné zdravotnictví